2010
DOI: 10.1007/s11164-010-0178-6
|View full text |Cite
|
Sign up to set email alerts
|

Propane combustion over supported Pd catalysts

Abstract: We prepared Pd catalysts supported on various metal oxides, viz. by an incipient wetness method and applied them to propane combustion. Several techniques: N 2 physisorption, inductively coupled plasma-atomic emission spectroscopy (ICP-AES), CO chemisorption, temperature-programmed reduction (TPR) and temperature-programmed oxidation (TPO) were employed to characterize the catalysts. Pd/SiO 2 -Al 2 O 3 showed the least catalytic activity at high temperatures among Pd catalysts supported on irreducible metal ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…9−11 Ceria can not only be used as the active component of the catalyst, 12−14 but also as the support of palladium (and other noble metals) catalysts for the oxidations of CO and propane and automotive emission control. 6,15 Since heterogeneously catalytic reaction occurs on the catalyst surface, the crystal planes exposed on the catalyst surface would affect obviously the catalytic performance, especially for the structure-sensitive catalytic reactions. 16−20 Recently, ceria nanocrystals with uniform and well-defined morphologies were controllably synthesized, the effect of ceria morphology on its catalytic performance was studied.…”
Section: Introductionmentioning
confidence: 99%
“…9−11 Ceria can not only be used as the active component of the catalyst, 12−14 but also as the support of palladium (and other noble metals) catalysts for the oxidations of CO and propane and automotive emission control. 6,15 Since heterogeneously catalytic reaction occurs on the catalyst surface, the crystal planes exposed on the catalyst surface would affect obviously the catalytic performance, especially for the structure-sensitive catalytic reactions. 16−20 Recently, ceria nanocrystals with uniform and well-defined morphologies were controllably synthesized, the effect of ceria morphology on its catalytic performance was studied.…”
Section: Introductionmentioning
confidence: 99%
“…The metallic Pd species plays an important role on the oxidation reaction at lower temperatures, such as CO oxidation. 6,7 On the other hand, oxidized Pd species shows higher activity for the methane oxidation, [8][9][10][11][12] which is rationalized by the role of dispersed Pd oxide species as an oxygen provider. [13][14][15] The oxidation state of supported Pd is strongly affected by the acid-base property of supports.…”
Section: Introductionmentioning
confidence: 99%
“…Propane is an attractive fuel, because it is a constituent of natural gas and can be delivered as liquefied petroleum gas (LPG) through well-developed infrastructure [3]. Propane combustion can be described as…”
Section: Introductionmentioning
confidence: 99%
“…Ishikawa et al [19] explained a high catalytic activity for propane combustion over Pt catalysts supported on solid superacids by the strong surface acidity of the support. Propane combustion over Pt catalysts on various supports, viz., MgO [11], Al 2 O 3 [11], SiO 2 -Al 2 O 3 [11,20], WO 3 [13], zeolite [21,22], TiO 2 -SiO 2 [23], and V 2 O 5 -Al 2 O 3 [7] has been examined. It has been reported that the activities of Pt catalysts on supports having high acidities was superior to those of Pt catalysts on supports having lower acidities, because the surface acidity of a support was considered to be a factor in the changing of the oxidation state of Pt [11,12,20,21,24].…”
Section: Introductionmentioning
confidence: 99%